Generative versus Discriminative Methods for Object Recognition - Ulusoy, Ilkay; Bishop, Christopher (In Proceedings IEEE International Conference on Computer Vision and Pattern Recognition, CVPR., San Diego., 2005)
Many approaches to object recognition are founded on probability theory, and can be broadly characterized as either generative or discriminative according to whether or not the distribution of the image features is modelled. Generative and discriminative methods have very different characteristics, as well as complementary strengths and weaknesses. In this paper we introduce new generative and discriminative models for object detection and classification based on weakly labelled training data. We use these models to illustrate the relative merits of the two approaches in the context of a data set of widely varying images of nonrigid objects (animals). Our results support the assertion that neither approach alone will be sufficient for large scale object recognition, and we discuss techniques for combining them.